Effect of apixaban, an oral and direct factor Xa inhibitor, on coagulation activity biomarkers following acute coronary syndrome - Becker, Richard C.; Alexander, John H.; Newby, L. Kristin; Yang, Hongqiu; Barrett, Yuchen; Mohan, Puneet; Wang, Jessie; Harrington, Robert A.; Wallentin, Lars C. (Thrombosis and Haemostasis, 2010)
Apixaban is an oral, direct factor Xa inhibitor under development for secondary prevention in acute coronary syndrome (ACS). Apixaban‘s effect on D-dimer and prothrombin fragment 1.2 (F1.2) (coagulation activity biomarkers ) was determined in a randomised, double-blinded, placebo-controlled, phase 2 study. Patients (n=1,715) with either ST-segment elevation or non-ST-segment elevation ACS received either placebo or apixaban 2.5 mg twice daily, 10 mg once daily, 10 mg twice daily or 20 mg once daily for six months. Samples were obtained at baseline (before study drug administration), week 3 and week 26. Apixaban plasma concentrations were measured directly by liquid chromatography/mass spectometry, and anti-Xa activity was determined using apixaban as a reference standard. D-dimer and F 1.2 were measured using ELISA-based methods. Most patients had elevated D-dimer and F1.2 levels at baseline. Both coagulation activity biomarkers decreased by week 3 in all treatment groups, but to a greater degree with apixaban than placebo (p<0.001). In a multivariable analysis, apixaban was independently associated with a change in biomarkers over time (p<0.0001). While the overall decrease did not differ significantly among the three highest apixaban doses, F1.2 was suppressed more rapidly by the 10 mg once daily than the 2.5 mg twice daily dose (p<0.05). There was a strong and direct relationship between apixaban plasma concentrations and anti-Xa-apixaban levels, and an inverse relationship for both measures with coagulation activity biomarkers. In conclusion, the oral direct factor Xa inhibitor apixaban significantly reduced coagulation activity biomarkers among patients with ACS. The 10 mg once daily dose reduced thrombin generation (F 1.2) and fibrin formation (D-dimer) more rapidly and robustly than the 2.5 mg twice daily dose. The effect on both D-dimer and F 1.2 was apixaban concentration-and factor Xa inhibition dependent, durable and provided general guidance for dose selection in phase 3 investigation.
Keywords: Apixaban; oral factor Xa antagonists; acute coronary syndrome